Ketahanan Tiga Varietas Jahe terhadap Fusarium oxysporum f. sp. zingiberi in Vitro dan in Planta - Dyah Pancasiwi; Soedarmono Soedarmono; Endang Mugiastuti; Loekas Soesanto (Jurnal Fitopatologi Indonesia, 2013)
Fusarium oxysporum f. sp. zingiberi is the causal agent of dry rot on ginger and could highly effect ginger production. Resistant variety is one of disease control strategy that is recommended. Various ginger varieties are available but their response to F. oxysporum f. sp. zingiberi has not been reported. In this study three ginger varieties were evaluated for their resistence to F. oxysporum f. sp. zingiberi based on in vitro and in planta inoculalation method. Gadjah and Emprit varieties were considered moderately susceptible whereas Merah varieties was moderately resistance to F. oxysporum f. sp. zingiberi. pathogen will be indicated.Key words: dry rot disease, ginger var. Merah, resistant variety, resistance